(untitled) (Web of Discoveries: Journal of Analysis and Inventions, 2024)
In this article, a comprehensive study of the mechanism of taxation of indirect taxes, a scientific proposal for improving the mechanism of taxation and effective tax administration and practical recommendations are highlighted.